Use of tricalcium silicate to evaluate asphalt absorption on steel slag: Atomic simulation and micro-scale characterization. (June 2021) - Liu, Jinzhou; Yu, Bin; Wang, Shuyi; Li, Lu; Zhang, Jiaqiang
Abstract: The study investigated asphalt absorption on steel slag at molecular- and micro-scale. The diffusion of saturate, aromatic, resin, and asphaltene (SARA) was evaluated using tricalcium silicate as a representative of steel slag. Specifically, atomic structures of asphalt were observed using molecular dynamics (MD). Ultraviolet and nanoindentation tests eventually verified the simulative findings. Results denote that SARA diffuses in accordance with Arrhenius's law. Due to the electron density and polarity, resins and asphaltenes perform higher diffusion rates near steel slag. The colloid structure of asphalt is more sensitive to moisture contents. The interior pores in steel slag exhibit fluorescence effect and tend to absorb non-polar components of asphalt with lower moduli and hardness, which agrees well with the distribution found via MD. The interfacial bonding of steel slag-asphalt under the coupling of temperature and humidity is weakened due to the variation of colloid structure of asphalt and the self-association of asphaltenes.